1990
DOI: 10.1103/physrevlett.65.492
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic x-ray dichroism in core-level photoemission from ferromagnets

Abstract: We report on the novel effect of magnetic x-ray dichroism in core-level photoemission from ferromagnets with circularly polarized radiation. Depending on the relative orientation of photon spin and sample magnetization (parallel or antiparallel), a single emission line may be resolved into two lines, due to exchange splitting of the core level. The mechanism is explained in terms of spin-selective dipole transitions in the presence of spin-orbit coupling. Possible applications of magnetic x-ray dichroism in ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
107
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(112 citation statements)
references
References 17 publications
(2 reference statements)
4
107
0
1
Order By: Relevance
“…The dichroism changes its sign across the 2p spectra in the sequence: − + +−, which is characteristic for an exchange-type m j sublevel ordering. 19 The details of the MCDXPS reveal small deviations from this simple expectation. For example, the MCDXPS remains positive in the region between the spin-orbit doublet.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dichroism changes its sign across the 2p spectra in the sequence: − + +−, which is characteristic for an exchange-type m j sublevel ordering. 19 The details of the MCDXPS reveal small deviations from this simple expectation. For example, the MCDXPS remains positive in the region between the spin-orbit doublet.…”
Section: Resultsmentioning
confidence: 99%
“…17,18 In the case of magnetic circular dichroism in x-ray photoemission spectroscopy (MCDXPS), however, where electrons are excited into states far above the Fermi energy, the origin of the dichroic effect is not obvious. 19 It has been argued that the dichroism is due to the splitting of the core level states, which in turn, is caused by a combination of spin-orbit coupling and exchange interaction with the valence band electrons. 19 The origin and magnitude of the core level exchange splitting was introduced ad hoc and it remained undecided whether the exchange splitting is a ground-state property or a final state effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8] Linearly and circularly polarized EUV and soft X-ray radiation is routinely generated at large-scale facilities such as electron storage rings and free-electron lasers -unique sources of high energy photons in terms of intensity, photon energy range, spectral bandwidth, pulse duration, and polarization. Therefore, a complete polarization analysis is usually performed at synchrotrons with sophisticated polarimetric and ellipsometric instruments.…”
Section: Introductionmentioning
confidence: 99%
“…Baumgarten et al [8] carried out a pioneering study on magnetic dichroism in photoemission and observed this phenomenon in the core-level spectra of transition metals. The effect, however, was rather small (few %) because of the limited resolution of the experiment.…”
Section: Introductionmentioning
confidence: 99%